Efficacy of Mirror Biofeedback Rehabilitation on Synkinesis in Acute Stage Facial Palsy in Children. Issue 7 (August 2021) - Baba, Shintaro; Kondo, Kenji; Yoshitomi, Ai; Kanemaru, Asako; Nakaya, Muneo; Yamasoba, Tatsuya
Abstract : Objectives: To evaluate the efficacy of mirror biofeedback rehabilitation for synkinesis in severe acute facial paralysis in children. Methods: Eight pediatric patients with facial paralysis with an initial electroneurography (ENoG) value less than 10% who underwent mirror biofeedback rehabilitation (the child-rehabilitation group) were enrolled. Seven infants (under age 2 yr) who were unable to undergo rehabilitation (the infant-and-toddler control group) and adult patients (n = 13, range, 33–56 yr) who underwent rehabilitation (the adult-rehabilitation group) comprised the control groups. All the patients enrolled were baseline House–Brackmann (H–B) grade VI at onset. The patients began daily facial biofeedback rehabilitation using a mirror at the first sign of muscle contraction on the affected side and were instructed to keep their eyes symmetrically open using a mirror during mouth movements. The training was continued for 12 months after the onset of facial paralysis. The degree of oral-ocular synkinesis was evaluated by the degree of asymmetry in eye opening width during mouth movements. The synkinesis index was calculated as a percentage of the interpalpebral space width ([normal side – affected side]/normal side). Statistical analyses used non-parametric tests (the Kruskal–Wallis test and Steel–Dwass posthoc test). Results: The synkinesis index was significantly lower in the child-rehabilitation group than in the infant-and-toddler control group or the adult-rehabilitation group ( p < 0.001). Conclusion: Children who underwent mirror biofeedback rehabilitation had less synkinesis than the infant-and-toddler control group, suggesting that mirror biofeedback rehabilitation is more effective in preventing the exacerbation of synkinesis in children.